Comprehensive validation of transient stability calculations in electric power systems and hardware-software tool for its implementation; IEEE Access; Vol. 8 - Suvorov A. A. Aleksey Aleksandrovich; Diab A. A. Z. Ahmed A. Zaki; Gusev A. S. Alexander Sergeevich; Andreev M. V. Mikhail Vladimirovich; Askarov A. B. Alisher Bakhramzhonovich; Ufa R. A. Ruslan Alexandrovich; Razzhivin I. A. Igor Andreevich; Kievets A. V. Anton Vladimirovich; Bay Yu. D. Yuly Dmitrievich; Rudnik V. E. Vladimir Evgenevich; Aboelsaud Raef Siam Sayed Ahmed; Ibrahim Ahmed I. M. Ibrahim Mohamed; et al. (2020, 2020)
Title screen